Antibiotic prescription policy for acute otitis media: do we follow the guidelines?. (19th July 2021) - Marom, Tal; Shefer, Galit; Tshori, Sagi; Mingelgrin, Shira; Pitaro, Jacob
Abstract: Background: Acute otitis media (AOM) is a common cause for antibiotic prescription. Most guidelines endorse abstaining from immediate antibiotic treatment ('watchful waiting', WW) in mild–moderate episodes. We studied adherence rates to the latest AOM guidelines (2013), in terms of antibiotic type and prescription options. Methods: In this population-based study, AOM episodes were identified in Clalit Health Services-insured children aged 0–10 years between 2011 and 2018, using a data-sharing platform. After identifying the index, prescription and issuing dates for antibiotics for each AOM episode, treatment was categorized as immediate (≤2 days after diagnosis) or WW (antibiotic not prescribed/issued; prescribed ≤2 days after diagnosis but issued on Days 2–7; or prescribed/issued on Days 2–7). Guideline adherence was measured according to age. Results: Of the 491 106 episodes, 361 518 (73.6%) were treated with antibiotics. Following the 2013 guidelines, the ratio of episodes in children aged ≤6 months that were adherent (immediate treatment) was higher (OR = 1.22; 95% CI 1.15–1.29; P < 0.001), whereas the adherent episode ratio for children aged 6–24 months and 2–10 years (WW) was lower (OR = 0.87; 95% CI 0.85–0.88 and OR = 0.94; 95% CI 0.92–0.96, respectively; P < 0.001). Antibiotic prescription rates after 2013 for children aged ≤6 months were not different (OR = 1.03; 95% CI 0.96–1.1; P = 0.4), but were higher in children aged 6–24 months and 2–10 years (OR = 1.07; 95% CI 1.05–1.09; P < 0.001 and OR = 1.02; 95% CI 1.01–1.04; P = 0.015, respectively). Amoxicillin was the most common antibiotic, administered in 75.6% of episodes. Azithromycin was most commonly associated with treatment failure (6.6%). Conclusions: Improved adherence to the 2013 guidelines was observed only in children aged ≤6 months and over-treatment with antibiotics was still high.